Opinion 2/13 of the Court (C.J.E.U.). (April 2016) - Halberstam, Daniel
Abstract : Opinion 2/13 of the Court of Justice of the European Union (CJEU) declared the draft agreement on European Union accession to the European Convention on Human Rights (ECHR) incompatible with the Treaty on European Union. The Opinion comes toward the end of a long and gradual process of incorporating human and fundamental rights principles into the legal system of the European Community and its successor, the European Union. Opinion 2/13 sends the Commission back to the drawing board on what has long been seen as the capstone of that process—EU accession to the Strasbourg human rights regime as an external check on human rights protection within the European Union.